How Do Teacher Creativity, Parental Guidance, Learning Methods and Interest in Learning Affect the Quality of Student Learning in Elementary Schools? - Muhammad Hasan; Amalia Amalia; Tuti Supatminingsih; Nurdiana Nurdiana; Nurjannah Nurjannah (Universitas Pendidikan Ganesha, 2023)
Many factors determine the quality of student learning at the basic education level. Several factors have been studied, but several still need to be studied specifically, resulting in theoretical gaps. This study aims to analyze the influence of teacher creativity, parental guidance, learning methods, and interest in learning on students' learning quality at the basic education level. This research was conducted with a quantitative approach. Informants in this study were 50 parents of students. This research instrument uses a closed questionnaire sheet. Instrument testing is carried out by testing the validity and reliability tests. The data were analyzed using multiple regression analysis with the t-test and F-test. The results showed that the variables of teacher creativity, learning methods, and learning interest partially did not significantly affect students' learning quality. Only parental guidance has a significant influence on the quality of student learning. However, when viewed simultaneously, all the independent variables, starting from teacher creativity, parental guidance, learning methods, and interest in learning, significantly affect the quality of learning.